High Stakes Require More Than Just Talk: What to Do About Corruption in Health Systems; Comment on "We Need to Talk About Corruption in Health Systems" - Taryn Vian (Kerman University of Medical Sciences, 2019)
Reluctance to talk about corruption is an important barrier to action. Yet the stakes of not addressing corruption in the health sector are higher than ever. Corruption includes wrongdoing by individuals, but it is also a problem of weak institutions captured by political interests, and underfunded, unreliable administrative systems and healthcare delivery models. We urgently need to focus on corruption as a health systems problem. In addition to supporting research to better understand the context and implications of corruption in health systems, this article suggests actions that public health professionals can do now to fight corruption.